Arm Anthropometric Ratios in peruvian schoolchildren - Pajuelo Ramírez, Jaime (1998)
We have studied the nutritional status of schoolchildren by arm anthropometric ratios. 1 525 children between 6 - 9 years of age were studied. The data is a representative sample of Peru, and belongs to the Survey of Nutritional Status of the Peruvian Inhabitant (Estado Nutricional del Poblador Peruano «ENPPE»). The ratios are Arm Circumference (AC) and Triceps Skinfold (TS) related with age. With AC and TS, Arm Muscle Area (AMA) and Arm Fat Area (AFA) were calculated. Measures were taken following the recommended international methodology. The reference sample used was the Frisancho´s one. About 44% and 23% of children have an AC and TS smaller than 10p, respectively. In both ratios the prevalence of children over 90p does not exceed 3%. For AFA, 32,6% of girls and 25,9% of boys are below 10th; for AMA, male have the largest prevalence (32,3%; female 27,7%). Prevalence over 90p does not exceed 2%. AC and TS average for different ages rank between 10 and 25p and about 25p from reference sample, respectively. 16,3 and 3,2% of children are over 85p of body mass index and TS (obesity), respectively. Only 1,8% of children ranks over 85p for both ratios. AC, TS, AMA and AFA are nutritional storage ratios, which shows a sharp detriment of magre and fatty mass in a great number of children.